Welfare and Rational Care. - Darwall, Stephen (Princeton Monographs in Philosophy, 2008)
What kind of life best ensures human welfare? Since the ancient Greeks, this question has been as central to ethical philosophy as to ordinary reflection. But what exactly is welfare? This question has suffered from relative neglect. And, as Stephen Darwall shows, it has done so at a price. Presenting a provocative new "rational care theory of welfare," Darwall proves that a proper understanding of welfare fundamentally changes how we think about what is best for people. Most philosophers have assumed that a person's welfare is what is good from her point of view, namely, what she has.